Rotor vibration control studies with electrorheological fluid lubricant in floating ring bearings. (May 2019) - Mutra, Rajasekhara Reddy; Srinivas, J
The high-speed rotors are usually supported on fluid-film bearings such as single film hydrodynamic bearings and floating ring type bearings to attain high damping capacity for minimizing the resonant vibration amplitudes. However, the bearing forces are highly nonlinear and are often prone to stability issues in the system. This work presents the use of an electrorheological fluid as a lubricant in floating ring bearings for rotor vibration control. The unbalance response of the rotor system is obtained from finite element approach by accounting gyroscopic effects and nonlinear bearing forces. By idealizing the electrorheological lubricant using Bingham model, the effective Reynolds equations for inner and outer films are formulated in terms of film pressures and thickness values. The coupled differential equations are solved numerically and the effect of external applied electric field on the dynamic response is studied in detail. A case study of automotive turbocharger rotor system is selected for illustration.